The role of profitability in moderating the influence of capital structure on dividen policy - Abas, Muhammad Rida; Leon, Farah Margaretha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This research aims to analyze profitability in moderating the influence of capital structure on dividend policy. The research method uses quantitative methods with the object of research was conducted at Consumer Non-Cyclicals Sector companies listed on the Indonesia Stock Exchange (IDX) with a time period of 2019-2023. Sampling using purposive sampling with a total observation of 155 samples and using secondary data derived from the company's annual financial statements. The data analysis method uses panel data regression with Eviews tools. The results showed that capital structure through debt to assets ratio has a significant negative effect on dividend policy, while debt to equity ratio and asset structure have a significant positive effect on dividend policy. The profitability proxied by return on assets has a significant positive effect on dividend policy. Profitability is also able to significantly moderate (weaken) the effect of capital structure on dividend policy. This research is expected to provide information for investors in making investment decisions by paying attention to the company's healthy capital structure, high profitability level, and consistent implementation of dividend policies. Recommendations for future researchers can add other variables such as liquidity ratios, conduct research on different objects or increase the research time period.